Piracy in the Gulf of Guinea: The Role of UNODC in Combating Maritime Crime - Luqmanulhakim, Naufal; Putri Hernanda, Aulia; Arvianas, Nerissa; Priambodo Pradipo, Satrio; Satria, Randhi (Kemudi, 2023)
The Gulf of Guinea is a center of maritime crime, which harms seafarers, shipping companies, and other countries that conduct international trade by sea. United Nations Office on Drugs and Crime (UNODC) is a United Nations organization whose role is to address international organized crime issues including ship piracy. The United Nations Office on Drugs and Crime has conducted various programs to combat maritime crimes around the world including in the Gulf of Guinea (Gulf of Guinea). This research uses a qualitative research method with a descriptive analysis approach and uses secondary data sourced which is obtained from written materials collected through literature studies. Through the concept of maritime security, this study analyzes the role of the United Nations Office on Drugs and Crime in tackling piracy in the Gulf of Guinea and concludes various factors that lead to piracy, such as political, social, and economic. This research is important to understand the United Nations Office on Drugs and Crime’s efforts in dealing with pirates in the Gulf of Guinea and will contribute to the treaty on combating transnational organized crime. This research highlights the role of the United Nations Office on Drugs and Crime in combating piracy in the Gulf of Guinea. Through cooperation with several African nations, the case of piracy has been declining in the past several years. The research found that the United Nations Office on Drugs and Crime’s role in dealing with piracy in the Gulf of Guinea has not been fully optimized due to several factors that cause piracy to persist, some of the factors including the political issues, lack of law integration between the country, and non-contribution from the leaders of the pirate organization in the authorities' investigations.